Anastomotic Airway Complications After Lung Transplant: Clinical, Bronchoscopic and CT Correlation. Issue 5 (September 2016) - Luecke, Kyle; Trujillo, Camilo; Ford, Jonathan; Decker, Summer; Pelaez, Andres; Hazelton, Todd R.; Rojas, Carlos A.
Abstract : The purpose of this article is to review the normal appearance and common complications of the airway anastomosis in lung transplant patients with emphasis on computed tomography images with bronchoscopic correlation. The spectrum of complications will be presented as early (<1 mo after transplant) or late (>1 mo). Variations in surgical technique as well as presentation and management options for airway complications will also be discussed.